The Ancestry and Ethnic Milieu of the Caucasian Muslim Nokhchis (Chechens) - Kopanski, Ataullah Bogdan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Ancestry and Ethnic Milieu of the Caucasian Muslim Nokhchis (Chechens)